Nationhood, executive power and the Australian constitution - Stephenson, Peta (London [England] : Hart Publishing, 2022)
"The first comprehensive study of the nature and scope of the nationhood power, this book brings a fresh perspective to the scholarship on the powers of the executive branch in Australia. The question of when the Federal Executive Government can act without the authorisation of the Parliament is contested and highly topical in Australia. In recent judicial decisions, Australian courts have suggested that statutory authorisation may not be required where the Federal Executive Government is exercising the nationhood power; that is, the implied executive power derived from the character and status of the Commonwealth as the national government. The Federal Executive Government has relied on this power to implement controversial spending programs, respond to national emergencies and exclude non-citizens from Australia. Together, the chapters in this book analyse and evaluate judicial observations about the operation of the nationhood power in these different contexts and its relationship with the other categories of federal executive power in s 61 of the Constitution. While the focus of this book is on the nationhood power, it also addresses broader issues concerning the relationship between the legislative and executive branches in parliamentary systems of government. This book makes an important contribution to the literature on executive power and will appeal to constitutional lawyers, scholars and practitioners and those who are involved in the administration of government."--
1. Introduction I. The Relationship Between Parliament and the Executive in Australia II. Overview and Structure of the Book III. The Scope of the Inquiry -- 2. The Executive Power of the Commonwealth I. The Drafting History of Section 61 of the Australian Constitution II. Australia's Attainment of Independence in the Exercise of Federal Executive Power III. Categories of Federal Executive Power in Australia IV. The Nationhood Power V. A Conceptual Framework: The 'Breadth' and 'Depth' of Federal Executive Power -- 3. The Nationhood Power and Commonwealth Spending I. The Australian Assistance Plan Case II. The Application of the Nationhood Power in Davis v Commonwealth III. The Nationhood Power and Commonwealth Spending Programs Following the Pape and Williams Decisions IV. The Scope of the Nationhood Power -- 4. The Nationhood Power, Internal Security and Civil Emergencies I. The Constitutional Framework II. The Use of the Australian Defence Force for Internal Security and Civil Emergencies III. Sources of Federal Executive Power IV. The Nationhood Power, the Prerogative and the Australian Defence Force V. The Relationship between Federal Executive Power and Part IIIAAA of the Defence Act 1903 (Cth) -- 5. The Nationhood Power and Border Protection I. The Tampa Case II. The Expansion of Federal Executive Power in the Tampa Case III. The Relationship between Federal Executive Power and the Migration Act 1958 (Cth) -- 6. Limits on the Nationhood Power I. The Nationhood Power and Section 61 of the Australian Constitution II. Federalism as a Limit on the Nationhood Power III. The Relationship between the Nationhood Power and Statute IV. Conclusion -- Bibliography -- Index
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Federal government -- Australia; Executive power -- Australia; Constitutional law -- Australia; Australia -- Politics and government; Electronic books